How MUI Fatwa Changes Indonesia Mindset towards Pro-Israel Boycott Products using the Naïve Bayes Classification Method - Susi Jumiati; Dodi Vionanda; Admi Salma (UNP Journal of Statistics and Data Science, 2024)
Boycotting pro-Israel products has become a popular topic on social media, both in Indonesia and globally. This research aims to analyze the sentiments of Indonesian using the Naive Bayes classification method regarding the boycott before and after the issuance of MUI Fatwa No.83/2023. Through sentiment and word cloud analysis of 3327 tweets, it was found that discussions remained consistent and were not influenced by MUI Fatwa. The sentiment of the majority of Indonesian regarding the boycott of pro-Israel products is positive, with full support for this action. MUI Fatwa has had an impact on the sentiment of Indonesian, as can be seen from the increase in positive sentiment after the fatwa was released. Word cloud analysis shows that both before and after November 8, 2023, the top one word that appears in the word distribution is exactly the same, namely 'boycott'. This similarity shows that the discussion topics that developed on the Twitter platform remained consistent, both before and after the release of MUI Fatwa Indonesian netizens have uniformly discussed boycotting products that support Israel as a form of rejection of the genocide carried out by that country in Gaza, Palestine.